Linking substrate and nucleus via actin cytoskeleton in pluripotency maintenance of mouse embryonic stem cells - Brit Gracy David; Hideaki Fujita; Kyota Yasuda; Kazuko Okamoto; Yulia Panina; Junya Ichinose; Osamu Sato; Masanobu Horie; Taro Ichimura; Yasushi Okada; Tomonobu M Watanabe (Stem Cell Research, 2019)
Pluripotency of mouse embryonic stem cells is regulated by transcription factor regulatory networks as well as mechanical stimuli sensed by the cells. It has been unclear how the mechanical strain applied to the plasma membrane is transferred to the nucleus in mouse embryonic stem cells (mESCs). We here investigated the machinery of the mechanotransduction based on the finding that spontaneous differentiation of mESCs was inhibited with the downregulation of ROCK2 in cells attached to soft substrates. On examining the effects of actin bindings to both focal adhesions and cell junctions in cells on soft substrates, co-localization of actin filaments and α-catenin, which links actin to E-cadherin, decreased after differentiation induction. Also, disrupting actin-nucleus mechanical link through dominant negative assay of Nesprins helps to sustain the pluripotency genes; thus, revealing that mechanical strain relayed by actin-Nesprin connection is required for the initiation of the differentiation process. Keywords: Embryonic stem cells, Stem cell pluripotency, Nesprin